Case report: Fully endoscopic microvascular decompression for trigeminal neuralgia - Jiang, Haotian; Zou, Dewei; Wang, Pan; Zeng, Longwei; Liu, Jie; Tang, Chao; Zhang, Gang; Tan, Xiaorong; Wu, Nan (Frontiers in Neurology, 2023)
Due to the advantages of being safe, effective, and micro-invasive, microvascular decompression has become the mainstream treatment for trigeminal neuralgia, glossopharyngeal neuralgia, hemifacial spasm, etc. Initially, microvascular decompression has been performed under a microscope, which limited the light and visualization to a certain extent. With the development of endoscope technology, the endoscope has been applied to microvascular decompression, which further improves the visualization range and light. The purpose of this study is to investigate the efficacy of fully endoscopic microvascular decompression in the treatment of trigeminal neuralgia. We reviewed 3 patients with trigeminal neuralgia who underwent fully endoscopic microvascular decompression. After surgery, the facial pain of all patients was significantly relieved. And, there were no obvious postoperative complications and no recurrence after 6 months of follow-up. The excellent surgical outcomes indicate that fully endoscopic microvascular decompression is an effective and safe method for the treatment of trigeminal neuralgia. Furthermore, it also shows that the endoscope has certain advantages and popularization significance in microvascular decompression.